A comparative analysis of selected recommendations of the feng shui school of form, Alexander et al.’s pattern language, and findings of environmental psychology - Kryžanowski, Špela (Urbani izziv, 2019)
Feng shui is a traditional Chinese art of creating a supportive living environment. Despite many research contributions on feng shui, very few verify (comparatively or experimentally) the actual effectiveness of feng shui recommendations. Even the architectural profession has never clearly denied its opinion on feng shui. is comparative analysis seeks to determine whether 118 selected feng shui school of form recommendations are consistent with the recommendations of Alexander et al.’s pattern language and with selected findings in environmental psychology. The results support this, showing that 34% of the recommendations (or forty recommendations out of 118 in total) are consistent with pattern language and that 45% (or fifty-three recommendations) are fully or partially consistent with the findings of environmental psychology. Altogether, more than half of the recommendations (57%, or sixty-seven recommendations) are consistent (indirectly confirmed) by one or the other knowledge system, which means that it is very likely that these recommendations will actually have the promised impact on users of physical space. Twenty-seven feng shui recommendations (or 23% out of the 118) are doubly consistent, of which most are related to the five-animals feng shui model, the importance of the presence of water and natural light in the living environment, and the importance of the main entrance. The bulk of the recommendations, which remain unaddressed, relate to the Chinese concept of living energy, or qi.